The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.21699/jns.v5i3.370
|View full text |Cite
|
Sign up to set email alerts
|

Right Congenital Diaphragmatic Hernia Associated With Hepatic Pulmonary Fusion: A Case Report

Abstract: We present a case of male newborn presented with respiratory distress at 21 hours of life. The patient was operated for right congenital diaphragmatic hernia (CDH). Hepatic pulmonary fusion (HPF) was found at surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…Only 22 cases of HPF were identified (Table 1). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The embryological basis for development of HPF is not yet understood. One theory for this development is that failure in formation of the diaphragm during early gestation allows hepatic tissue to herniate into the chest during the 10th week of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Only 22 cases of HPF were identified (Table 1). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The embryological basis for development of HPF is not yet understood. One theory for this development is that failure in formation of the diaphragm during early gestation allows hepatic tissue to herniate into the chest during the 10th week of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…A redoubtable complication, which appears in right-sided hernias, is hepatic pulmonary fusion, an extremely rare condition (only 14 cases in litera-ture, most of them in the neonatal period/ infancy). Hepatic and pulmonary tissue fuse by a fibrous band, broncho-biliary fistula or anomalous drainage from the right lung to the intrahepatic inferior vena cava are findings related to HPF (9).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic pulmonary fusion was first reported by Katz et al in 1998[7] and 17 cases have been reported in the English literature [7][8][9][10][11][12][13][14][15][16][17][18]. Among these, 6 patients died and the prognosis is poor [7,8,10,13,18].…”
Section: Discussionmentioning
confidence: 99%